HATE SPEECH DAN BULLYING PADA ANAK BERKEBUTUHAN KHUSUS (Studi Kasus di Sekolah Inklusi Model di Kabupaten Gresik) - MUHAMMAD ARFAN MU'AMMAR (Universitas Muhammadiyah Prof Dr Hamka, 2017)
Inclusive education is a further consequence of the education Global Policy fo All proclaimed by UNESCO 1990. The education policy is an effort to create the human right in education declared in the Universal Declaration of Human Rights of 1949. The logical consequence of these rights is, all children have the right to receive an education that does not discriminate on the basis of physical barriers, ethnicity, religion, language, gender and ability. Inclusive education declared in the World Conference on Education, in Salamanca, Spain, 1994 mentioned that fundamental principle of inclusive education included students with disabilities in the same class together with other normal students, without exception. The integration of normal and disablelities cause some frictions in the class. It also causes inconvenient relations among the students. Frequently, the normal students will dominate the class. They ridicule the disable students. This situation create impacts such as inferiority, lack of learning spirit even the most poor one they have no will to go to school. This study in inclusion school model in Gresik tried to explore the effects of hate Speech and bullying and tried to find solutions on this phenomenon.